ChemInform Abstract: Chemical and Pharmacological Progress on Polyacetylenes Isolated from the Family Apiaceae. Issue 26 (June 2015) - Chen, Yuemei; Peng, Shiyi; Luo, Qiongzhi; Zhang, Juan; Guo, Qiang; Zhang, Yuan; Chai, Xingyun
Abstract Review: 107 refs.